Health consequences of using special diets with restricted carbohydrate consumption - Maria Janowska; Karolina Rogacka; Bartłomiej Pyrak; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2022)
Introduction and purpose: There are many reasons why patients with specific health disorders, as well as people in good health, decide to follow special diets. Often their choice falls on dietary models that include limited carbohydrate intake. The most popular in this area are low-carbohydrate and high-protein diets, which have a significant impact on metabolism, making them of particular interest to people with excessive body weight.  State of knowledge: Low-carbohydrate diets include many dietary models of varying restrictiveness, with or without achieving a state of ketosis. The ketogenic diet has the most promising clinical results in terms of effects on carbohydrate and fat metabolism. Long-term studies are still too few and inconsistent, also regarding the effects on weight loss compared to traditional approach. High-protein diets also include a reduction in carbohydrate intake, but with a higher protein content. Observations on the effect of weight reduction and metabolic modification are inconsistent. The possible multi-directional negative health effects seem to be a strong argument against recommending this approach. Conclusion: The basis of any reduction diet must be a reduced energy supply. This can be achieved in a variety of ways, which are designed to facilitate its implementation by patients, as well as to have the most beneficial effect on their impaired metabolism. Diversions from the traditional approach may have beneficial effects, but may also contribute to other health problems. It is important to consider the patients' health status as a whole, and to ensure specialist follow-up when using described special diets, because of possible side effects and difficulties in properly balancing the diet. They can only be recommended in specific cases. The standard in the management of excessive body weight remains the traditional approach, the effects of which are well documented and do not represent risk factors for other conditions.